THE EFFECT OF PREHEATING AT 39o AND 60o ON COMPRESSION STRENGTH OF BULK-FILL COMPOSITE RESIN - Rinawati Satrio; Ryana Budi Purnama; Arwin Diva Nafida (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: The incremental placement technique for composite resin may lead to bond failures and air entrapment between resin layers. Bulk-fill composite resin, which can be applied to cavities depths of up to 4 - 5 mm, is expected to have good compressive strength so that it can resemble natural tooth structures. Purpose: This study aimed to evaluate the effect of preheating on the compression strength of bulk-fill composite resins at 39oC and 60oC. Method: This research type was a laboratory experiment employing a post-test control group design. A total of 27 cylindrical bulk-fill composite resin specimens were divided into three groups: group 1 was preheated at 39oC, group 2 at 60oC, and group 3 served as the control group. The samples were then immersed in distilled water and stored in an incubator at 37oC for 48 hours. Compressive strength test was measured using a Universal Testing Machine. Result: One-way ANOVA statistical test showed that there were significant differences in the three groups (p-value < 0.05). A post-hoc Bonferroni test was carried out to compare between groups and indicated a significant difference between the 600C preheated group and the control group. Conclusion: Preheating at 39oC and 60oC affects the compression strength of bulk-fill composite resin.